Peranan Komunikasi Efektif PenasehatAkademik Mahasiswa (Kajian Manajemen Komunikasi) - Hasan, Yummil (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Effective communication can be measured through five criterions, they are indicator of understanding, pleasure, influencing attitudes, social relations are getting better, and revealing to an action. Communication of Student’ Academic Advisory in giving explanations and guidance, gives consideration to students in selecting courses, providing guidance and advice that are intended to assist students in achieving the success of the study and in order to develop a scientific attitude and a good habit and also give warning to student’s low academic performance. It can be said to be quite good for the cause of understanding and it can be seen on the indicator of understanding. Furthermore, Academic Advisor in communicating the role can also be classified as a good indicator of pleasure, indicator of affected attitude, the indicator of social relationships, and revealing to an action